THE EFFECT OF POPULATION,INVESTMENT AND REGIONAL EXPENDITURE AGAINST REGIONAL INCOME AND HUMAN DEVELOPMENT INDEX IN BERAU DISTRICT, EAST BORNEO INDONESIA: THE EFFECT OF POPULATION,INVESTMENT AND REGIONAL EXPENDITURE AGAINST REGIONAL INCOME AND HUMAN DEVELOPMENT INDEX IN BERAU DISTRICT, EAST BORNEO INDONESIA - Endah Susanti (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2019)
This study aims to examine the Effect of Population,Investment and Regional Expenditure against Regional Income and Human Development Index of Berau District during period 2014-2018. This research is a causality research that analyze the direct and indirect effect of some independent variables and on the dependent variable by using path analysis. Variable used is variable of Population and Investment and Fregional Expenditure to regional income and Human Development Index of Berau district. The results showed that the variable of population, and Regional Expenditure did not directly affect the regional income in Berau District. The investment variable has a direct and significant effect on the regional income in Berau District. The variable of population, investment, Expenditure, and regional income did not significantly affect the human development index in Berau District. Variables of population, investment, regional expenditure indirectly affect the human development index through regional income in Berau District